2008
DOI: 10.1080/13546800802355666
|View full text |Cite
|
Sign up to set email alerts
|

Developing hypnotic analogues of clinical delusions: Mirrored-self misidentification

Abstract: Introduction. Despite the prevalence of delusional beliefs there are currently no viable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 42 publications
4
33
0
Order By: Relevance
“…For instance, when determining memory source, certain qualitative features such as memory perspective may inappropriately provide strong evidence that an event was self-experienced. In turn, other qualitative features of a memory, such as the consistency of an event with other autobiographical knowledge, may not be given appropriate importance (for a similar Downloaded by [University Library Utrecht] at 02:39 15 March 2015 argument in a hypnotic delusion of mirrored-self misidentification, see Barnier, Cox, et al, 2008). To examine this possibility, future research could examine whether a hypnotic delusion (such as of misidentification) is associated with susceptibility to source errors for autobiographical events.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, when determining memory source, certain qualitative features such as memory perspective may inappropriately provide strong evidence that an event was self-experienced. In turn, other qualitative features of a memory, such as the consistency of an event with other autobiographical knowledge, may not be given appropriate importance (for a similar Downloaded by [University Library Utrecht] at 02:39 15 March 2015 argument in a hypnotic delusion of mirrored-self misidentification, see Barnier, Cox, et al, 2008). To examine this possibility, future research could examine whether a hypnotic delusion (such as of misidentification) is associated with susceptibility to source errors for autobiographical events.…”
Section: Discussionmentioning
confidence: 96%
“…Drawing together findings from these experiments and our other recent work, the elements required to create a viable hypnotic analogue of delusions include: (a) high hypnotizable participants (who preferably receive a formal hypnotic induction; see below for further discussion of this issue), (b) a credible delusion suggestion that can be understood and interpreted appropriately (we explored different versions of the suggestion because in previous work on hypnotic mirrored-self misidentification one of the versions we selected was ineffective; Barnier, Cox, et al, 2008), (c) techniques to index self-change (e.g., self-discrepancy and "I am" tasks), (d) objective and subjective indices of response to the suggestion (e.g., objective measures include providing a name and self-description following the suggestion; subjective measures include postexperimental and EAT inquiry comments), (e) challenges to the suggested delusion (e.g., contradiction and confrontation), and (f) techniques to index the impact of the delusion on information processing (e.g., autobiographical memory elicitation, and selective encoding and/or recall as used by Burn et al, 2001; see also Cox, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other relevant personality measures ought to be explored, in particular suggestibility and absorption, which correlate with susceptibility to hypnosis (Braffman and Kirsch, 1999); a relatively recent model of psychosis that is beginning to be employed in delusion research (Barnier et al, 2008).…”
Section: Genetic Effectsmentioning
confidence: 99%
“…First, Connors et al (2013) examined the role of the hypnotic induction and the specific suggestion in the analogue. In particular, they directly compared this new Factor 1 suggestion to impair face processing with Barnier et al (2008)'s earlier suggestion for mirrored-self misidentification (referred to as a ''fully-formed'' suggestion because it directly specified the content of the delusion; i.e., that they would see a stranger), in both hypnosis and wake conditions. Connors et al found that the Factor 1 suggestion was just as effective as the fully-formed suggestion in generating a hypnotic analogue of mirrored-self misidentification, despite not directly specifying the intended experience to participants.…”
Section: Impaired Face Processing As Factormentioning
confidence: 99%
“…This delusion occurs most frequently in dementia Connors, Langdon, & Coltheart, 2015) and is difficult to study because of the accompanying clinical symptoms. To examine whether hypnosis could be used to recreate the features of this clinical delusion, Barnier et al (2008) focused on recreating the belief that one's reflection in the mirror was not oneself. They gave 12 high hypnotisable participants a hypnotic induction and one of three different hypnotic suggestions to model potential experiences of the delusion.…”
Section: Mirrored-self Misidentificationmentioning
confidence: 99%